Assessment of the effectiveness of the training programs on mango processing in the Province of Guimaras - Villegas, Philip Daynos (Iloilo City University of the Philippines in the Visayas, 2006)
The study was conducted to assess the effectiveness of the training programs on mango processing implemented by the Technology Demonstartion Center (TDC) in the Province of Guimaras. It aimed to analyze the extent of effectiveness of the program structure, trainees capabilities, organization management, and the participants' characteristics on mango processing. A total of 33 trainees' served as respondents' in a survey questionnaire data resulted were analyzed using simple descriptive statistical tools e.g. percentages, frequencies distribution and central tendency measurements (Mean, Median, and Mode). A follow-up discussion with the individual members of the training management staff was also conductedto explore related issues and concerns. The results indicate that most of the trainees cannot sustain the processing entrepreneurial activities due to insufficiency of capital to finance theproduction processing and inadequacy of mango raw fruits due to seasonality. However, the trainees perceived a high degree of effectiveness in terms of trainings they had with TDC. Theyattributed to these, their enhanced level of knowledge and skills and their improved income of (5%) due to applications of their new practices learned from the training. The result showedissues and needs to reconsider in the training program. There is a need to intensify, revitalize and institutionalize some facets of the training to sustain its effectiveness. The following arerecommended : The proper selection of participants and institutionalize the standard criteria and selection process ; integration and addition of these modules in the training : marketing development strategy, finance management, product development and business management ; involvement finance institutions, institutionalize reaction, learning and impact evaluations ; and establishments of strong linkages with institutions relating to training and development.
[Research Paper[ (Management 299 : Research Methods in Manaagment) -- Iloilo City : U. P. in the Visayas, [2006].